The Role of Women’s Farmer Groups as An Alternative Solution to Food Insecurity during The Covid -19 Pandemic - Amalia, Fisy; Mayndarto, Eko Cahyo (Faculty of Economics and Business, Hasanuddin University, 2022)
Research on the Az Zahra Women's Farmer Group in the Buaran South Tangerang area which was carried out from March 2021 to August 2021 with the title The Role of Women's Farmer Groups as Alternative Solutions to Food Insecurity during the Covid-19 Pandemic in Buaran, Serpong, South Tangerang. The data taken are primary and secondary data, primary data is taken from observations and interviews with officials, supervisors and members of the women's farmer group. The results of environmental observations and interviews conducted can be seen that the group has succeeded in achieving group managerial effectiveness. The results of the observations are seen from the data at the time of the initial formation (in 2018) and the data at the time the research was conducted (in 2021). The initial data for the formation of the Women Farmers Group are: The area of cultivated land is 300m2, with 29 members, 2 types of plants that can be harvested, the value of the harvest is Rp. 1,740,000. a year. While the results of operations in 2021, the number of plants will be 25 types of plants, the area of land being cultivated will be 10,000 m2 and the welfare level of members will be Rp. 12,500,000 a year. In terms of organizational management, this group has proven that it has carried out managerial effectiveness in order to achieve the group's goals as indicated by the increasing area of land planted, growing crop yields and increasing welfare of members although they do not have the land. This group that has performed its management functions well, such as planning, organizing, directing and controlling. The role of the Women Farmers group in preventing food insecurity is very effective, because the harvest obtained can prevent food insecurity in the family as well as the surrounding community by providing food in the form of vegetables and health plants, as well as by making donations to local residents in need.